To burn or not to burn : the question of straw burning and nitrogen fertilization effect on nitrous oxide emissions in sugarcane - Chalco Vera, Jorge Elias; Valeiro, Alejandro Hector; Posse Beaulieu, Gabriela; Acreche, Martin Moises (2017)
Nitrous oxide (N2O) is the main greenhouse gas emitted from farming systems and is associated with nitrogen (N) fertilizer application as well as decomposition of organic matter present in the environment. The objective of this study was to determine the effect of post-harvest straw burning and synthetic N fertilization on the dynamics of N2O emissions in the sugarcane-soil system in Tucuman, Argentina, compared with a native forest. Close-vented chambers were used to capture N2O during three consecutive growing seasons. The highest N2O emissions from the sugarcane-soil system coincided with the period of high soil and air temperatures, rainfall and soil N content. The effect of synthetic N fertilization on annual cumulative N2O emission was 7.4–61.5% higher in straw burned than in unburned treatments, especially during a wet growing season. There was a significant effect of treatments on N2O emission factors among growing seasons: 0.58–1.67% and 0.94–3.34% in the unburnt and burnt treatments, respectively. The emission factors for sugarcane are highly dependent on rainfall, temperature and crop management practices; regarding the latter, avoiding straw burning and reducing N soil availability, assessing alternative N fertilizers or new application modes such as split rates, seem to be the key for mitigating N2O emissions from the sugarcane-soil system in Tucumán, Argentina.